INFLUENCE OF WORK MOTIVATION AND WORK DISCIPLINE ON THE PERFORMANCE OF EMPLOYEES IN REGIONAL GENERAL HOSPITAL IN THE DISTRICT DEMANG SEPULAU RAYA CENTRAL LAMPUNG - M. Oktaviannur; Adhetya Pratama (UBL, 2016)
This study aims to determine Influence Of Work Motivation And Work Discipline On The Performance Of Employees In Regional General Hospital District Demang Sepulau Raya Central Lampung. Data collected through questionnaires and conducted on 40 employees of the General Hospital of Demang Sepulau Raya. Analysis of the data in this study using SPSS version 18. Mechanical testing of the data used in this study include tests of validity by factor analysis, reliability test with Cronbach's Alpha, multiple linear regression analysis, to test and prove the hypothesis of the study, T test to determine the effect of partial and F test to determine the effect simultaneously or whole. The results showed that working motivation has positive influence on employee performance and discipline of work has positive influence on employee performance. In simultaneous F test or test work showed that motivation and work Discipline positive effect simultaneously on Employee Performance.